Meningkatkan Kinerja Guru Bahasa dalam Melaksanakan Pelajaran - Kartini, Tini (Journal of Education Action Reseach, 2018)
This study aims to determine the performance of language teachers in teaching at SMK Negeri 30 Jakarta, by looking at student learning outcomes for language subjects (Indonesian, English, French) for students of class XI semester one of the school year 2017/2018 that have not reached the standard KKM determined by the school. This research is School Action Research (PTS) through the implementation of Scheduled Guidance. This research was carried out at 30 State Vocational Schools Jakarta and its implementation in two cycles, each cycle in the study included four steps namely (1) planning (2) implementation (acting), (3) observation (observing), (4) reflection (reflecting). Data were collected using observation sheets and analyzed using descriptive analysis. Based on research data and discussion, it can be concluded that the implementation of Guidance is scheduled for language teachers. proven to be able to improve the performance of language teachers in implementing learning for class XI students. The first semester of SMK Negeri 30 Jakarta in the 2017/2018 academic year, so that student learning outcomes improve well.